Preparation method of coaxial cellulose-based aerogel fiber fabric for daytime radiation refrigeration

By introducing hollow silica microspheres and high pore structures into cellulose-based aerogel fiber fabrics, coaxial wet spinning and atmospheric pressure drying technology, the shortcomings of existing passive radiation-cooled fiber fabrics in solar reflectivity and cooling efficiency are solved, and efficient daytime radiation refrigeration effect and good mechanical properties are achieved.

CN119877168AActive Publication Date: 2025-04-25SICHUAN UNIV

Patent Information

Application Number
CN202411864120.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing passive radiation-cooled fiber fabrics have shortcomings in solar reflectivity and cooling efficiency, and the nanomaterial coating affects softness and functional particles are prone to fall off. The high pore structure and weak interface binding force of composite aerogel fibers lead to deterioration of mechanical properties, and large-scale manufacturing faces challenges.

Method used

Using the preparation method of coaxial cellulose-based aerogel fiber fabric, hollow silica microspheres are dispersed in a cellulose solution to form a mixed spinning liquid, and gel fibers are obtained by coaxial wet spinning, followed by normal pressure drying and woven processing to form cellulose aerogel fibers with good interfacial bonding performance and high porosity.

Benefits of technology

It improves the thermal insulation performance and mechanical strength of cellulose aerogel fiber, reduces thermal conductivity, enhances the solar reflectivity and atmospheric window emissivity, while maintaining good flexibility and breathability, solving the shortcomings of traditional fiber fabrics in daytime radiation cooling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877168A_ABST
    Figure CN119877168A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a coaxial cellulose-based aerogel fiber fabric for daytime radiation refrigeration, which is characterized in that coaxial fibers take pure cellulose as a core, a skin layer comprises hollow silicon dioxide and low-concentration cellulose, and the hollow silicon dioxide is uniformly dispersed in the cellulose; the preparation method comprises the following specific steps: S1, preparing hollow silicon dioxide with an adjustable particle size; s2, preparing a hollow silicon dioxide / cellulose mixed spinning solution; s3, dissolving cellulose; s4, carrying out coaxial wet spinning; s5, carrying out multi-step solvent replacement; s6, performing continuous normal-pressure drying; s7, weaving fibers; the woven aerogel fiber fabric can effectively scatter sunlight, and the solar reflectivity (gt; 92%), and the emissivity (gt; 96%); the preparation method is green and environment-friendly, the operation is simple, the continuous and large-scale production of the cellulose-based aerogel fiber can be realized, and the prepared coaxial aerogel fiber fabric can show excellent radiation refrigeration performance in the daytime.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of radiation refrigeration materials, and in particular to a method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiation refrigeration. Background Art

[0002] Passive radiative cooling materials, with their ultra-high solar reflectivity (0.3–2.5 μm) and selective emission of thermal radiation to the cold outer space through the atmospheric transparent window (8–13 μm), provide a promising candidate for efficient cooling of buildings and humans without consuming any energy. By developing passive radiative cooling fabrics, textiles can be used to protect the human body in hot weather.

[0003] Cellulose fiber is one of the most abundant biological resources in nature. It has a large number of hydroxyl functional groups and carbon-oxygen bonds, which make it have a high emissivity in the "atmospheric window". However, pure cellulose fiber has low solar reflectivity under direct sunlight, and its cooling efficiency is very limited. By further introducing nanomaterials, the micro-nano structure of cellulose fiber can be regulated to improve its reflectivity in the visible light-near infrared band, thereby inhibiting the absorption of solar energy and realizing the wide-band light management ability of cellulose. Patent 202210426528.X discloses that inorganic cooling materials such as magnesium oxide or magnesium hydroxide are deposited on the surface of cellulose acetate fabric by a coating method. However, these inorganic particle coatings affect the softness of passive radiation cooling fiber fabrics, and the coating materials inevitably face the problem of functional particle shedding when repeatedly washed and rubbed. To meet this challenge, another strategy is to prepare fibers by randomly blending and spinning micro-nano particles, but when the surface temperature of the material is lower than the ambient temperature, it is easy to absorb heat from the surrounding environment by convection heat transfer, resulting in an increase in the surface temperature of the material and a reduction in the cooling effect.

[0004] Cellulose aerogel fibers have sufficient refractive index (n~1.5) to enhance the optical path difference, thereby causing high solar reflection, while high porosity produces low thermal conductivity, providing a new way to resist the parasitic heat transfer problem of the surrounding environment. Cost-effective large-scale radiative cooling can be achieved by adopting multi-scale structural design and randomly dispersed nanoparticles. However, the high porosity structure and weak interfacial bonding force of composite aerogel fibers also lead to the deterioration of their mechanical properties, which is a huge obstacle to the practical application of composite functional aerogel fibers. In addition, large-scale fiber manufacturing also faces huge challenges. It is urgent to develop a relatively low-cost, simple to prepare, and continuously produced cellulose composite aerogel fiber preparation technology to produce cellulose aerogel fibers with a clear microstructure for daytime radiative cooling. Summary of the invention

[0005] In view of the above defects, the problem solved by the present invention is to provide a method for preparing coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling, comprising the following steps:

[0007] S1, mixing water, anhydrous ethanol, hexadecyltrimethylammonium bromide, ammonia water and ethyl orthosilicate, and performing a hydrolysis reaction to obtain solid silica microspheres; washing the solid silica microspheres with anhydrous ethanol and water by centrifugation, and removing the template by stirring and etching; washing with anhydrous ethanol and water by centrifugation alternately, and obtaining hollow silica microspheres after drying;

[0008] S2, dispersing the hollow silica microspheres of S1 in a cellulose solution to form a mixed solution; mixing cellulose in the mixed solution, and centrifugally degassing to obtain a hollow silica / cellulose mixed spinning solution;

[0009] S3, dispersing pure cellulose in cellulose dissolving solution, and degassing by centrifugation to form a pure cellulose solution;

[0010] S4, the hollow silica / cellulose mixed spinning solution of S2 is filled in the coaxial needle sheath, the pure cellulose solution of S3 is filled in the core, the sheath / core layer solution is uniformly injected into the coagulation bath containing tert-butyl citric acid water at a certain flow rate, and the gel fiber is obtained by coaxial wet spinning;

[0011] S5, introducing the gel fiber of S4 into an alcohol dehydrating agent replacement tank and a short-chain alkane solution replacement tank in sequence, and drying at normal pressure to obtain a coaxial cellulose aerogel fiber;

[0012] S6. Processing the coaxial cellulose aerogel fibers of S5 into cellulose-based aerogel fiber fabrics according to a weaving method.

[0013] In a preferred embodiment of the present invention, in S1, the mass ratio of water to anhydrous ethanol is in the range of 1:0.5-3, the mass ratio of hexadecyltrimethylammonium bromide, ammonia water and tetraethyl orthosilicate is in the range of 0.5-0.7:3-5:3-5, and the mass ratio of water to tetraethyl orthosilicate is in the range of 6-10:1-3.

[0014] In a preferred embodiment of the present invention, in said S1, the particle size of the hollow silica microspheres is 200 to 1200 nm, and the hollow diameter is 100 to 800 nm.

[0015] In a preferred embodiment of the present invention, the solvent in the cellulose dissolving solution is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid, and the cellulose is one of bamboo pulp, cotton pulp and wood pulp.

[0016] In a preferred embodiment of the present invention, in S2, the solid content of the hollow silica / cellulose mixed spinning solution is 3-5 wt%; the mass ratio of the hollow silica to the cellulose is 1:9-3:7.

[0017] In a preferred embodiment of the present invention, in said S3, the cellulose content in the pure cellulose solution is 7-9wt%.

[0018] In a preferred embodiment of the present invention, in S4, the core layer flow rate of the coaxial wet spinning is 30 to 50 μL - 1 min -1 , sheath flow rate is 50~100μL -1 min -1 ; The coaxial outer needle model is 15~18G, and the inner needle model is 20~23G; the primary gel fiber extrusion speed is 20~40m / h.

[0019] In a preferred embodiment of the present invention, in S5, the alcohol dehydrating agent is at least one of ethanol, ethylene glycol, tert-butanol, and isopropanol; the short-chain alkane is at least one of n-pentane, n-hexane, n-heptane, and n-octane; and the replacement time is 20 to 60 minutes.

[0020] In a preferred embodiment of the present invention, in said S6, the cover factor of the woven aerogel fiber woven fabric is 0.7-0.9.

[0021] In a preferred embodiment of the present invention, in S1, the hydrolysis reaction is carried out at 30-40° C. for 20-30 hours to obtain solid silica microspheres, and the centrifugal speed is 4000-8000 r / min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The hollow silica prepared by the present invention has rich hydroxyl groups on its surface, so that even a high proportion of hollow particles can be evenly dispersed in the cellulose solution. At the same time, the hollow microspheres provide more pores and store more still air, which can greatly improve the overall thermal insulation performance of the aerogel fiber and reduce thermal conductivity.

[0024] 2. The coaxial cellulose-based aerogel fiber prepared by the present invention has cellulose as the base material for both the cortex and the core, and has good interface bonding performance, sustainability and green environmental protection. The prepared fiber has a large specific surface area and pore volume, and the porosity is 80-93%.

[0025] 3. The core layer of the coaxial cellulose-based aerogel fiber prepared by the present invention has a high cellulose concentration, and the obtained aerogel structure is more compact, providing good mechanical support for the aerogel fiber. The outer layer contains hollow silica functional particles, which have poor interface bonding with the low-concentration fibers. The fibers are prone to stress concentration and breakage during stretching. The core layer mainly bears most of the stress and improves the mechanical strength of the entire composite fiber. The mechanical properties of the composite fiber are 1.8 times higher than those of the composite fiber without a coaxial structure.

[0026] 4. The aerogel fiber drying method adopted in the present invention can be dried quickly under normal pressure. This novel drying method mainly utilizes the low surface tension of short-chain alkanes and quickly removes the solvent at high temperature. This method can increase the skeleton strength of the gel network, prevent excessive shrinkage deformation and structural damage during the drying process, and can achieve high porosity and low density of aerogel fibers. In addition, the method is simple to operate, safe and reliable, and can continuously produce aerogel fibers, which is much faster than traditional freeze-drying or supercritical CO2 technology, and avoids the use of sealing equipment required under high pressure or vacuum conditions. This technology can meet the needs of continuous and large-scale production of aerogel fibers.

[0027] 5. The coaxial cellulose-based aerogel fiber prepared by the present invention has good solar reflectivity (>92%) and atmospheric window emissivity (>96%), and has low thermal conductivity (<0.66Wm -1 K -1 ), which can avoid parasitic heat reducing the radiant cooling efficiency.

[0028] 6. The core layer of the present invention uses bamboo pulp cellulose, whose high crystallinity and complex microstructure provide excellent mechanical strength and low thermal conductivity, ensuring that the fiber is not easy to break during the stretching process and effectively preventing heat conduction; while the sheath layer uses wood pulp cellulose, whose low crystallinity and easy modification characteristics enable it to be combined with nanoparticles such as hollow silica microspheres, significantly enhancing light scattering and reflection performance and improving solar reflectivity. This combination of core layer and sheath layer optimizes the effect of daytime radiation cooling through the synergistic effects of mechanics, optics and thermal management, while maintaining good flexibility and air permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 Flow chart of the preparation of coaxial cellulose-based aerogel fibers of the present invention;

[0031] Figure 2 This is a microscopic morphology of the surface of the coaxial cellulose-based aerogel fiber of Example 1 of the present invention;

[0032] Figure 3 This is a microscopic morphology of the cross section of the coaxial cellulose-based aerogel fiber of Example 1 of the present invention;

[0033] Figure 4 It is a comparison diagram of solar reflectivity and mid-infrared emissivity curves of Example 2 of the present invention and Comparative Example 1;

[0034] Figure 5 This is the radiation cooling performance of Example 2 of the present invention under direct sunlight.

[0035] In the figure: 1-core spinning solution; 2-sheath spinning solution; 3-coaxial needle; 4-pulling roller; 5-coagulation bath; 6-alcohol dehydrating agent; 7-short-chain alkane; 8-high-temperature drying channel; 9-collecting roller. DETAILED DESCRIPTION

[0036] like Figure 1 As shown, the present invention provides a method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiation cooling, comprising the following steps:

[0037] S1, mixing water, anhydrous ethanol, hexadecyltrimethylammonium bromide, ammonia water and ethyl orthosilicate, and performing a hydrolysis reaction to obtain solid silica microspheres; washing the solid silica microspheres with anhydrous ethanol and water by centrifugation, and removing the template by stirring and etching; washing with anhydrous ethanol and water by centrifugation alternately, and obtaining hollow silica microspheres after drying;

[0038] S2, dispersing the hollow silica microspheres of S1 in a cellulose solution to form a mixed solution; mixing cellulose in the mixed solution, and centrifugally degassing to obtain a hollow silica / cellulose mixed spinning solution;

[0039] S3, dispersing pure cellulose in cellulose dissolving solution, and degassing by centrifugation to form a pure cellulose solution;

[0040] S4, the hollow silica / cellulose mixed spinning solution of S2 is filled in the coaxial needle sheath, the pure cellulose solution of S3 is filled in the core, the sheath / core layer solution is uniformly injected into the coagulation bath containing tert-butyl citric acid water at a certain flow rate, and the gel fiber is obtained by coaxial wet spinning;

[0041] S5, introducing the gel fiber of S4 into an alcohol dehydrating agent replacement tank and a short-chain alkane solution replacement tank in sequence, and drying at normal pressure to obtain a coaxial cellulose aerogel fiber;

[0042] S6. Processing the coaxial cellulose aerogel fibers of S5 into cellulose-based aerogel fiber fabrics according to a weaving method.

[0043] In some specific embodiments, the cellulose in S2 is selected from wood pulp cellulose, and the cellulose in S3 is selected from bamboo pulp cellulose;

[0044] The preparation method of wood pulp cellulose comprises: cutting eucalyptus into small segments of 1-3 mm, removing impurities through mechanical screening and air separation, steaming with 10-15% NaOH solution at 150-200° C. for 2-3 hours, then bleaching with 2-3% hydrogen peroxide for 0.5-1 hour, dissolving in tetrabutylammonium hydroxide / urea solution (TBAH / urea / water=2:2:3), controlling the dissolution temperature to 30-40° C. and the dissolution time to 1-2 hours, and finally centrifugally degassing (4000 r / min, 10 minutes) to obtain bamboo pulp cellulose with a crystallinity of 40-50% and a polymerization degree of 1000-1500.

[0045] The preparation method of bamboo pulp cellulose comprises: cutting bamboo into small segments of 1-3 mm, removing impurities through mechanical screening and air separation, steaming with 15-20% NaOH solution at 150-200° C. for 2-3 hours, then bleaching with 2-3% hydrogen peroxide for 0.5-1 hour, dissolving in tetrabutylammonium hydroxide / urea solution (TBAH / urea / water=2:2:3), controlling the dissolution temperature to 30-40° C. and the dissolution time to 1-2 hours, and finally centrifugally degassing (5000 r / min, 15 minutes) to obtain bamboo pulp cellulose with a crystallinity of 65-75% and a polymerization degree of 1200-1600.

[0046] In some specific embodiments, in S1, the mass ratio of water to anhydrous ethanol is in the range of 1:0.5-3, the mass ratio of hexadecyltrimethylammonium bromide, ammonia water and tetraethyl orthosilicate is in the range of 0.5-0.7:3-5:3-5, and the mass ratio of water to tetraethyl orthosilicate is in the range of 6-10:1-3.

[0047] In some specific embodiments, in S1, the particle size of the hollow silica microspheres is 200-1200 nm, and the hollow diameter is 100-800 nm.

[0048] In some specific embodiments, the solvent in the cellulose dissolving solution is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid, and the cellulose is one of bamboo pulp, cotton pulp and wood pulp.

[0049] In some specific embodiments, in S2, the solid content of the spinning solution in the hollow silica / cellulose mixed spinning solution is 3-5 wt%; and the mass ratio of the mixed solution to the cellulose is 1:9-3:7.

[0050] In some specific embodiments, in S3, the cellulose content in the pure cellulose solution is 7-9 wt%.

[0051] In some specific embodiments, in S4, the core layer flow rate of the coaxial wet spinning is 30 to 50 μL -1 min -1 , sheath flow rate is 50~100μL -1 min -1 ; The coaxial outer needle model is 15~18G, and the inner needle model is 20~23G; the primary gel fiber extrusion speed is 20~40m / h.

[0052] In some specific embodiments, in S5, the alcohol dehydrating agent is at least one of ethanol, ethylene glycol, tert-butanol, and isopropanol; the short-chain alkane is at least one of n-pentane, n-hexane, n-heptane, and n-octane; and the replacement time is 20 to 60 min.

[0053] In some specific embodiments, in S6, the cover factor of the knitted aerogel fiber woven fabric is 0.7-0.9.

[0054] In some specific embodiments, in S1, the hydrolysis reaction is carried out at 30-40°C for 20-30 hours to obtain solid silica microspheres, and the centrifugal speed is 4000-8000 r / min.

[0055] like Figure 2-Figure 4 As shown, the specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0056] The following example

[0057] The wood pulp cellulose is the bamboo pulp cellulose with a crystallinity of 50% and a degree of polymerization of 1200 prepared by the above process; the bamboo pulp cellulose is the bamboo pulp cellulose with a crystallinity of 70% and a degree of polymerization of 1500.

[0058] Example 1

[0059] The present invention provides a method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling, comprising the following steps:

[0060] S1. a) Mix water and anhydrous ethanol in a mass ratio of 1:2, then add hexadecyltrimethylammonium bromide, ammonia water and ethyl orthosilicate in a mass ratio of 0.64:4:4, and hydrolyze at 35°C for 24 hours to obtain solid silica microspheres; b) Wash the microspheres after the reaction by centrifugation twice with anhydrous ethanol and water respectively. Disperse the centrifuged silica in 70°C water and stir and etch for 48 hours to remove the hexadecyltrimethylammonium bromide template; c) Wash the etched silica by centrifugation alternately with anhydrous ethanol and water, and obtain hollow silica microspheres with a diameter of 1000nm after drying.

[0061] S2. Disperse 2 g of the hollow silica synthesized above in 140 ml of a mixed solution of tetrabutylammonium hydroxide / urea / water in a mass ratio of 2:2:3, and disperse it by ultrasonication at room temperature. Then, add 4 g of wood pulp cellulose to the mixed solution, fully dissolve it, and then degas it by centrifugation to obtain a mixed spinning solution containing hollow silica.

[0062] S3. Disperse 8 g of pure bamboo pulp cellulose in 100 ml of a mixed solution of tetrabutylammonium hydroxide / urea / water in a mass ratio of 2:2:3, stir thoroughly, and centrifuge for degassing after dissolving.

[0063] S4, gel fiber was spun using coaxial needles, the outer needle model was 17G, the inner needle model was 19G; the needle sheath was filled with hollow silica / cellulose mixed spinning solution, the core was filled with pure cellulose solution, the sheath solution flow rate was 80μL-1min-1, and the core solution flow rate was 40μL -1 min -1 The extruded spinning solution is uniformly injected into a coagulation bath containing tert-butyl citric acid and water in a mass ratio of 1:2:3.

[0064] S5. To remove the residual alkaline solvent and residual salt, the gel fiber is introduced into a fresh ethanol dehydrating agent replacement tank and a n-hexane solution replacement tank in turn, and both solvents are replaced for 50 minutes.

[0065] S6. After displacement, the coaxial cellulose wet gel fiber quickly passes through a high-temperature drying tank at 120 to 220° C., and is collected on a collecting roller to obtain the coaxial cellulose aerogel fiber.

[0066] S7. Processing the coaxial cellulose aerogel fibers into fabrics according to a weaving method, wherein the fabric cover factor is 0.9.

[0067] The obtained coaxial cellulose-based aerogel fiber has a diameter of 500 μm, and the core layer diameter accounts for 60% of the total fiber diameter.

[0068] Example 2

[0069] This embodiment is basically the same as embodiment 1, except that: S4 is: using coaxial needles to spin gel fibers, the outer needle model is 17G, the inner needle model is 21G; the needle sheath is filled with hollow silica / cellulose mixed spinning solution, the core is filled with pure cellulose solution, and the sheath solution flow rate is 90μL -1 min -1 , core solution flow rate 20μL -1 min -1 The extruded spinning solution is uniformly injected into a coagulation bath containing tert-butyl citric acid and water in a mass ratio of 1:2:3.

[0070] The obtained coaxial cellulose-based aerogel fiber has a diameter of 500 μm, and the core layer diameter accounts for 40% of the total fiber diameter. The obtained coaxial aerogel fiber has worse tensile properties, but better thermal insulation properties and lower thermal conductivity.

[0071] Example 3

[0072] This embodiment is basically the same as embodiment 1, except that the size of the hollow silica selected is 800 nm. In S1, a) water and anhydrous ethanol are uniformly mixed in a mass ratio of 1:1, and then hexadecyl trimethyl ammonium bromide, ammonia water and ethyl orthosilicate are added in sequence in a mass ratio of 0.64:4:4, and hydrolyzed at 35°C for 24 hours to obtain solid silica microspheres; b) the microspheres after the reaction are centrifuged and washed twice with anhydrous ethanol and water respectively. The centrifuged silica is dispersed in 70°C water and stirred and etched for 48 hours to remove the hexadecyl trimethyl ammonium bromide template; c) the etched silica is alternately centrifuged and washed with anhydrous ethanol and water, and dried to obtain hollow silica microspheres with a diameter of 800 nm.

[0073] Example 4

[0074] This embodiment is basically the same as embodiment 1, except that the size of the hollow silica selected is 1200 nm. In S1, a) water and anhydrous ethanol are uniformly mixed in a mass ratio of 1:3, and then hexadecyl trimethyl ammonium bromide, ammonia water and ethyl orthosilicate are added in sequence in a mass ratio of 0.64:4:4, and hydrolyzed at 35°C for 24 hours to obtain solid silica microspheres; b) the microspheres after the reaction are centrifuged and washed twice with anhydrous ethanol and water respectively. The centrifuged silica is dispersed in 70°C water and stirred and etched for 48 hours to remove the hexadecyl trimethyl ammonium bromide template; c) the etched silica is alternately centrifuged and washed with anhydrous ethanol and water, and dried to obtain hollow silica microspheres with a diameter of 1200 nm.

[0075] Example 5

[0076] This embodiment is basically the same as embodiment 1, except that the size of the hollow silica selected is 900 nm. In S1, a) water and anhydrous ethanol are uniformly mixed in a mass ratio of 1:1.5, and then hexadecyl trimethyl ammonium bromide, ammonia water and ethyl orthosilicate are added in sequence in a mass ratio of 0.64:4:4, and hydrolyzed at 35°C for 24 hours to obtain solid silica microspheres; b) the microspheres after the reaction are centrifuged and washed twice with anhydrous ethanol and water respectively. The centrifuged silica is dispersed in 70°C water and stirred and etched for 48 hours to remove the hexadecyl trimethyl ammonium bromide template; c) the etched silica is alternately centrifuged and washed with anhydrous ethanol and water, and dried to obtain hollow silica microspheres with a diameter of 900 nm.

[0077] Example 6

[0078] This embodiment is basically the same as embodiment 1, except that the size of the hollow silica selected is 700 nm. In S1, a) water and anhydrous ethanol are uniformly mixed in a mass ratio of 1:0.5, and then hexadecyl trimethyl ammonium bromide, ammonia water and ethyl orthosilicate are added in sequence in a mass ratio of 0.64:4:4, and hydrolyzed at 35°C for 24 hours to obtain solid silica microspheres; b) the microspheres after the reaction are centrifuged and washed twice with anhydrous ethanol and water respectively. The centrifuged silica is dispersed in 70°C water and stirred and etched for 48 hours to remove the hexadecyl trimethyl ammonium bromide template; c) the etched silica is alternately centrifuged and washed with anhydrous ethanol and water, and dried to obtain hollow silica microspheres with a diameter of 700 nm.

[0079] Example 7

[0080] This embodiment is basically the same as Embodiment 1, except that the cellulose in S2 is bamboo pulp cellulose.

[0081] Example 8

[0082] This embodiment is basically the same as Embodiment 1, except that the cellulose in S3 is wood pulp cellulose.

[0083] Comparative Example 1

[0084] This comparative example is basically the same as Example 1, except that: S4 uses a 17G ordinary needle to spin gel fiber instead of a coaxial needle; the needle is filled with a hollow silica / cellulose mixed spinning solution, the core is filled with a pure cellulose solution, and the spinning solution flow rate is 100 μL -1 min -1 The extruded spinning solution is uniformly injected into a coagulation bath containing tert-butyl citric acid and water in a mass ratio of 1:2:3.

[0085] The obtained cellulose-based composite aerogel fiber has a diameter of 500 μm, and the obtained homogeneous composite aerogel fiber is filled with the most silica particles, resulting in the worst tensile properties, but the best thermal insulation properties and the lowest thermal conductivity.

[0086] Comparative Example 2

[0087] This comparative example is basically the same as Example 1, except that: S4 uses a 17G ordinary needle to spin gel fiber instead of a coaxial needle; the needle is filled with pure cellulose solution, and the spinning solution flow rate is 100 μL -1 min -1 The extruded spinning solution is uniformly injected into a coagulation bath containing tert-butyl citric acid and water in a mass ratio of 1:2:3.

[0088] The obtained cellulose-based aerogel fiber has a diameter of 500 μm. The internal three-dimensional network of the obtained pure cellulose aerogel fiber is the densest and free of silica particles, resulting in the best tensile properties, but the worst thermal insulation properties and the highest thermal conductivity.

[0089] The test results of porosity, density, breaking strength, breaking elongation and thermal conductivity of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1.

[0090] Table 1: Test data of Examples 1 to 6 and Comparative Examples 1 to 2

[0091]

[0092]

[0093] The fiber obtained in Example 1 has a higher porosity (87.55%) and a lower density (0.19 g / cm 3 ), the breaking strength and breaking elongation are moderate, and the thermal conductivity is relatively low (0.62Wm -1 K -1 ), indicating that it has good comprehensive performance.

[0094] Example 2 Compared with Example 1, this example changes the model of the coaxial needle and the flow rate of the spinning solution, resulting in a decrease in the ratio of the core layer diameter to the total fiber diameter (40%). Although the thermal insulation performance is better (the thermal conductivity is slightly lower), the tensile performance is worse, which is due to the decrease in the overall strength of the fiber caused by the reduction of the core layer cellulose.

[0095] Example 3 selected a smaller hollow silica size (800nm). Although the performance of the obtained fiber was basically equivalent to that of Example 1, the reflectivity decreased and the radiation cooling performance decreased, which shows that the size of the hollow silica has a significant effect on the optical properties of the fiber.

[0096] Example 4 The size of the hollow silica particles was further increased (1200 nm), resulting in an increase in the spacing between the hollow silica particles inside the fiber, which affected the thermal insulation performance of the fiber. Although the porosity of the fiber was still high, the increase in the air convection inside the fiber due to the increase in the size of the hollow silica particles resulted in a slight increase in the thermal conductivity (0.65 Wm -1 K -1 ). At the same time, the larger hollow silica particles weakened the mechanical properties of the fiber to a certain extent, and the breaking strength and breaking elongation decreased compared with Example 1.

[0097] Example 5 further reduces the size of the hollow silica (900 nm), which is between Example 3 and Example 4. The hollow silica particles of this size form a relatively uniform distribution inside the fiber, which not only ensures the thermal insulation performance of the fiber, but also maintains the mechanical properties of the fiber to a certain extent. However, compared with Example 1, its porosity and density are slightly reduced, and the thermal conductivity is slightly increased (0.66 Wm -1 K -1 ), which is due to the fine-tuning of the internal structure of the fiber caused by the change in the size of the hollow silica particles.

[0098] Example 6 further reduces the size of the hollow silica (700 nm). Although this helps to increase the number and density of hollow silica particles inside the fiber, thereby improving the thermal insulation performance of the fiber, the excessively small particle size also leads to a decrease in the mechanical properties of the fiber. This is because small particles are more likely to form agglomerations or accumulations inside the fiber, affecting the uniformity and strength of the fiber. Therefore, the fiber of Example 6 performs poorly in terms of breaking strength and breaking elongation, and the thermal conductivity also increases (0.67 Wm -1 K -1 ), which is due to the combined effect of the heterogeneity of the fiber internal structure and the decline in mechanical properties.

[0099] Comparative Example 1 does not use a coaxial needle, but uses a common needle to spin the gel fiber. Although the prepared fiber has the highest porosity and the lowest thermal conductivity, the tensile property is the worst, which is caused by the inhomogeneity of the internal structure of the fiber.

[0100] Comparative Example 2 also did not use a coaxial needle and was not filled with hollow silica particles. The pure cellulose aerogel fiber obtained had the densest internal three-dimensional network and the best tensile properties, but the worst thermal insulation performance and the highest thermal conductivity, which indicates that the filling of hollow silica particles has a significant effect on the thermal insulation properties of the fiber.

[0101] like Figure 5As shown, cellulose aerogel fibers have good solar reflectivity to enhance the optical path difference, thereby causing high solar reflection, while high porosity produces low thermal conductivity, which can avoid parasitic heat and reduce the radiative cooling efficiency under direct sunlight.

[0102] In this embodiment 1, bamboo pulp cellulose with a high crystallinity (70%) is used in the core layer of the coaxial fiber. It contains more microfibrils and nano-scale pores, which enhances the mechanical properties of the fiber and provides more stress dispersion paths during the stretching process, avoiding fracture caused by stress concentration. The degree of polymerization of bamboo pulp cellulose is relatively high (1200-1600), which means that its molecular chain is longer, which helps to form a stable network, further reduces the heat conduction path, and enhances the heat insulation effect. The crystallinity of wood pulp cellulose in this embodiment 1 is relatively low (50%), the molecular chain arrangement is relatively loose, and the structure formed is relatively disordered. This low crystallinity makes wood pulp cellulose have better light scattering performance in the visible light and near-infrared bands. When light is irradiated to the fiber surface, the disordered molecular structure will scatter the light in multiple directions, increase the reflectivity of light, especially for the visible light and near-infrared bands in sunlight. There are many surface active sites of wood pulp cellulose, which are easy to react chemically or physically adsorb with other functional materials (such as hollow silica microspheres). The light scattering and reflection properties can be further enhanced by introducing nanoparticles such as hollow silica microspheres. Hollow silica microspheres themselves have a low refractive index and a large specific surface area, which can effectively scatter and reflect sunlight, especially in the visible and near-infrared bands, significantly improving the solar reflectivity.

[0103] In Example 7, the entire fiber is composed of bamboo pulp cellulose. Although the strength is guaranteed and the breaking strength is 18.9 MPa, its lower light scattering ability and reflection performance will lead to increased absorption of sunlight, affecting the effect of daytime radiation cooling.

[0104] In Example 8, the entire fiber is wood pulp cellulose, and the thermal conductivity is relatively low (0.59 Wm -1 K -1 ), but the degree of polymerization of wood pulp cellulose is low, the molecular chain is short, the strength is insufficient, and the fiber is easy to break during the stretching process.

[0105] Summary: Based on the above analysis, it can be seen that Example 1 shows good comprehensive performance in terms of porosity, density, breaking strength, breaking elongation and thermal conductivity. Although other embodiments have been improved or optimized in some aspects, they are often accompanied by the sacrifice of other properties. Therefore, the preparation method of the coaxial cellulose-based aerogel fiber provided in Example 1 performs best in balancing various performance indicators.

[0106] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling, characterized in that: The following steps are involved: S1, mixing water, anhydrous ethanol, hexadecyltrimethylammonium bromide, ammonia water and ethyl orthosilicate, and performing a hydrolysis reaction to obtain solid silica microspheres; washing the solid silica microspheres with anhydrous ethanol and water by centrifugation, and removing the template by stirring and etching; washing with anhydrous ethanol and water by centrifugation alternately, and obtaining hollow silica microspheres after drying; S2, dispersing the hollow silica microspheres of S1 in a cellulose solution to form a mixed solution; mixing cellulose in the mixed solution, and centrifugally degassing to obtain a hollow silica / cellulose mixed spinning solution; S3, dispersing pure cellulose in cellulose dissolving solution, and degassing by centrifugation to form a pure cellulose solution; S4, the hollow silica / cellulose mixed spinning solution of S2 is filled in the coaxial needle sheath, the pure cellulose solution of S3 is filled in the core, the sheath / core layer solution is uniformly injected into the coagulation bath containing tert-butyl citric acid water at a certain flow rate, and the gel fiber is obtained by coaxial wet spinning; S5, introducing the gel fiber of S4 into an alcohol dehydrating agent replacement tank and a short-chain alkane solution replacement tank in sequence, and drying at normal pressure to obtain a coaxial cellulose aerogel fiber; S6. Processing the coaxial cellulose aerogel fibers of S5 into cellulose-based aerogel fiber fabrics according to a weaving method.

2. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In S1, the mass ratio of water to anhydrous ethanol is in the range of 1:0.5-3, the mass ratio of hexadecyltrimethylammonium bromide, ammonia water and tetraethyl orthosilicate is in the range of 0.5-0.7:3-5:3-5, and the mass ratio of water to tetraethyl orthosilicate is in the range of 6-10:1-3.

3. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In the S1, the particle size of the hollow silica microspheres is 200 to 1200 nm, and the hollow diameter is 100 to 800 nm.

4. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: The solvent in the cellulose dissolving solution is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid, and the cellulose is one of bamboo pulp, cotton pulp and wood pulp.

5. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In the S2, the solid content of the hollow silica / cellulose mixed spinning solution is 3-5 wt%; the mass ratio of the hollow silica to the cellulose is 1:9-3:

7.

6. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In the S3, the cellulose content in the pure cellulose solution is 7-9wt%.

7. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In S4, the core layer flow rate of the coaxial wet spinning is 30 to 50 μL -1 min -1 , sheath flow rate is 50~100μL -1 min -1 ; The coaxial outer needle model is 15~18G, and the inner needle model is 20~23G; the primary gel fiber extrusion speed is 20~40m / h.

8. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In S5, the alcohol dehydrating agent is at least one of ethanol, ethylene glycol, tert-butanol, and isopropanol; the short-chain alkane is at least one of n-pentane, n-hexane, n-heptane, and n-octane; and the replacement time is 20 to 60 minutes.

9. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1, characterized in that: In the step S6, the cover factor of the woven aerogel fiber fabric is 0.7 to 0.

9. The method for preparing a coaxial cellulose-based aerogel fiber fabric for daytime radiant cooling according to claim 1 is characterized in that: In the S1, the hydrolysis reaction is carried out at 30-40° C. for 20-30 hours to obtain solid silica microspheres, and the centrifugal speed is 4000-8000 r / min.

Citation Information

Patent Citations

  • Method of preparing hollow silicon dioxide ball

    CN101318660A

  • Aromatherapy pillow capable of preventing cervical spondylosis and having antibacterial function

    CN106820836A

  • Preparation method of cellulose-toughened silicon dioxide aerogel

    CN107673730A

  • Preparation method of aerogel warm-keeping cloth

    CN114016312A

  • Polyimide / silica hybrid hollow fiber and method of producing the same

    JP2011246833A

Cited By

  • Radial high-elasticity aerogel fiber and application thereof

    CN121065856A

  • Radially highly elastic aerogel fibers and applications thereof

    CN121065856B

  • Thermal radiation refrigeration photon fiber fabric, preparation method thereof and wet spinning device

    CN122061272A

  • Preparation method of side-by-side composite regenerated polyester fiber

    CN122105671A